Analisis Faktor-Faktor Yang Dipertimbangkan Konsumen Dalam Pembelian Produk Perhiasan Emas Di Kota Denpasar - Suwastawa, I Putu Agus; Mandala, Kastawan (E-Jurnal Manajemen, 2014)
ABSTRACT The purpose of this study was to determine the factors that consumers consider the purchase of gold jewelery products in Denpasar, To find a variable that consumers consider the purchase of gold jewelery products in Denpasar and to determine the factors most dominant of the consumer in the purchase of products gold jewelery in Denpasar. This study totaled 100 respondents with a sampling technique used was accidental sampling technique. Based on the analysis it was found that there are four factors that affect the purchase of gold jewelery products in the city of Denpasar, promotion, product, collection, and friends. Factors promotion and product factors is the most dominant factor in the study. Variables represent factors promotional campaign. Variable products represent products of factors. Variables representing the collection of personal factors. As well, a friend of variables representing social factors.   Keywords : Promotional, Products, Collections, Friends
Keywords: Promotional, Products, Collections, Friends